Morphometric analysis of indigenous, exotic and crossbred chickens (gallus domesticus L.) In Rajshahi, Bangladesh - Islam, M Saiful; Dutta, Ripon Kumar (Journal of Bio-Science, 2011)
Context: The quantification of morphometric variations has been regarded as peripheral to the mechanistic study of development of a species. This is now changing because the rapidly advancing knowledge of development in post-genomic biology is creating a need for more refined measurements of the morphometric changes produced by genetic perturbations or treatments. Objective: To estimate the age at marketable size and body morphometric parameters of indigenous, exotic and crossbred chicken to use such parameters as discriminate variables and to investigate the relationships among the variables of the chicken breeds under study. Materials and Methods: Six chicken breeds namely an indigenous (non descriptive, Deshi), four exotics as Broiler, Cockerel, Fayoumi and RIR, and a crossbred called Sonali (RIR?× Fayoumi?), were used for the study. Results: Age and nine morphometric parameters viz., gross weight (GW), blood weight (BW), feather weight (FW), skin weight (SW), body weight after skinning (BWS), visceral weight (VW), offal weight (OW), net edible weight (NEW) and edible ratio (ER), were determined from a total of 30 adult chickens (6 breeds _ 5 replicates each). All the parameters except FW showed significant differences among the breeds (P<0.01). RIR showed the highest values for all parameters except ER, which was the highest in Cockerel (1.77±0.23) and the lowest in RIR (1.47±0.01). Association between GW and NEW was statistically significant in Indigenous (P<0.001), Sonali (P<0.01) and all exotics except Broiler (P<0.001). Conclusion: Present results indicate that Cockerel, Fayoumi, Indigenous and Sonali chickens are advantageous genotypes as they had higher ER values compared to Broiler and RIR breeds. Keywords: Gallus domesticus; body morphometric traits; net edible weight; edible ratio DOI: http://dx.doi.org/10.3329/jbs.v18i0.8782 JBS 2010; 18(0): 94-98